Resolving the tension of Jesus's mission in Matthew's ancient biography - Breen, Jerry D. (Library of New Testament studies, 2024)
Jerry D. Breen argues that reading Matthew, and all the Gospels, as ancient biography is the necessary next step for Gospel studies. In particular, Breen contends that more specific comparisons should be made between the Gospels and ancient literature. Breen stresses that this reading invites narrative critics to place more emphasis on examining the use of sources and the importance of intertextual and historical information that the author introduces to the text. Breen places emphasis on the relationship between Jews and non-Jews in ancient Galilee and Palestine, and challenges the long-supported theory that Jesus did not minister to non-Jews beyond two or three exceptions. Demonstrating that Jesus is inclusive of everyone who comes to him, even though he was sent primarily to the Jews. Breen argues that the portrait which Matthew creates is one of a Jewish Messiah who is on a mission to restore Israel so that the restored people of God can bless the nations. Concluding that rather than two conflicting missions, the audience of the gospel is encouraged to view the healing of non-Jews during Jesus's ministry as further proof that the Jewish Messiah is bringing restoration to Israel